S&M2 [videorecording (DVD)] (Blackened Recordings, 2020)
The live concert film from Metallica and the San Francisco Symphony features 20 songs (over 2.5 hours of music) from the two-night event that opened San Francisco?s new Chase Center, with many Metallica fan favorites and 2 classical songs chosen by San Francisco Symphony Musical Director Michael Tilson Thomas. The DVD features the concert and behind the scenes bonus footage.